Detection of Helicobacter-like organisms in Thoroughbred horses from Venezuela - Briceño, Abelardo Morales; Garcia, Francisco; Bermudez, Victor (Brazilian Journal of Veterinary Pathology, 2010)
The aim of this study was to detect the presence of Helicobacter infection in Thoroughbred in Venezuela. One hundred and thirty six Thoroughbreds with signs for Equine gastric ulcer syndrome (EGUS) were studied in the National Race Track La Rinconada Caracas Venezuela. Necropsies were performed in all horses and samples of gastric tissue were collected. The tissue samples were fixed in formalin and processed by conventional H&E techniques. Additionally, the special staining procedure of Warthin-Starry, Giemsa and Blue Toluidine were also carried out. Ureasa test: rapid ureasa test (commercial kit) was performing of gastric tissue. The damage of the gastric mucosae in the animals was categorized as 2/136 Grade 0 Epithelium is intact throughout; no hyperemia, no hyperkeratosis. Grade 1 Mucosa is intact but there are areas of hyperemia and/or hyperkeratosis 26/136. Grade 2 small, single or multi-focal erosions or ulcers 38/136. Grade 3 Large, single or multi-focal ulcers, or extensive erosions and sloughing 36/136. Grade 4 Extensive ulcers, with areas with deep submucosal damage 34/136. Using the Warthin-Starry special stain, Giemsa and Blue Toluidine with spiral-shaped bacteria were evidenced found in 52, Grade 1: 13/52, Grade 2: 10, Grade 3: 16, Grade 4: 13. There seemed to be no association between Warthin-Starry, Giemsa and Blue Toluidine stain with the grade and location of lesions. Urease activity was then demonstrated in fifty-two equine. To conclude, we detected the presence of Helicobacter Like Organisms in the gastric mucosa from thoroughbred horses with EGUS.